2017
DOI: 10.1071/an16079
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting summer infertility in the pig: could heat stress-induced sperm DNA damage negatively affect early embryo development?

Abstract: Abstract.Temperature is a crucial factor in mammalian spermatogenesis. The scrotum, pampiniform plexus, and cremaster and dartos muscles in mammals are specific adaptations to ensure sperm production in a regulated environment 4À6 C below internal body temperature. However, the limited endogenous antioxidant systems inherent in mammalian spermatozoa compounded by the loss of cytosolic repair mechanisms during spermatogenesis, make the DNA in these cells particularly vulnerable to oxidative damage. Boar sperm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 118 publications
2
20
0
Order By: Relevance
“…Heat stress induced by scrotal immersion in 428C water for 20 min also causes dissociation in X-Y chromosomes of mice and rats, leading to chromosomally unbalanced gametes, even in heat-adapted animals (van Zelst et al 1995). We postulate that the above mechanisms may play a significant role in inducing DNA damage in boar spermatozoa during periods of heat stress (Peña et al 2017).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Heat stress induced by scrotal immersion in 428C water for 20 min also causes dissociation in X-Y chromosomes of mice and rats, leading to chromosomally unbalanced gametes, even in heat-adapted animals (van Zelst et al 1995). We postulate that the above mechanisms may play a significant role in inducing DNA damage in boar spermatozoa during periods of heat stress (Peña et al 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Of concern is the fact that the high rates of sperm DNA fragmentation observed during the peak wet season in our study (without noticeable effect on sperm motility) may currently go undetected by pig industries in tropical and subtropical climates. Moreover, they could significantly contribute to the high rates of embryo loss and pregnancy failure observed in sows during summer infertility (Peña et al 2017). Didion et al (2009) reported that a sperm sample with greater than 6% DNA fragmentation could result in decreased farrowing rates and average number of piglets born.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, HS can have negative effects on testosterone, causing hypertrophy and weakening of Leydig cell function [55]. The sperm’s damaged DNA can determine abnormal spermatozoa, which could cause low male fertility and subsequently fewer surviving embryos [4,56,57]. Even if the sperm can fertilize eggs normally, embryos that have received an injured paternal genome could die, causing poor performance [58].…”
Section: Discussionmentioning
confidence: 99%